2018
DOI: 10.1038/s41598-018-24373-4
|View full text |Cite
|
Sign up to set email alerts
|

Social thermoregulation as a potential mechanism linking sociality and fitness: Barbary macaques with more social partners form larger huddles

Abstract: Individuals with more or stronger social bonds experience enhanced survival and reproduction in various species, though the mechanisms mediating these effects are unclear. Social thermoregulation is a common behaviour across many species which reduces cold stress exposure, body heat loss, and homeostatic energy costs, allowing greater energetic investment in growth, reproduction, and survival, with larger aggregations providing greater benefits. If more social individuals form larger thermoregulation aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…is relatively abundant; however, the availability of natural food in the study area declines steadily throughout the year as temperatures drop and winter snowfall makes foraging difficult and energetically costly (Majolo et al , ). Winter is a time of energetic deficit for Barbary macaques (Campbell et al, 2018 a , b ). This may shift the cost/benefit balance by making access to energy‐rich foods from tourists more valuable in autumn and winter: 38% of human‐macaque provisioning encounters in our study occurred within 20 m of a road (J. Waterman, unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is relatively abundant; however, the availability of natural food in the study area declines steadily throughout the year as temperatures drop and winter snowfall makes foraging difficult and energetically costly (Majolo et al , ). Winter is a time of energetic deficit for Barbary macaques (Campbell et al, 2018 a , b ). This may shift the cost/benefit balance by making access to energy‐rich foods from tourists more valuable in autumn and winter: 38% of human‐macaque provisioning encounters in our study occurred within 20 m of a road (J. Waterman, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…data). This consideration of energy balance affects selection of sleeping sites by Barbary macaques (Campbell et al , 2018 b ), and also their social behavior (Campbell et al , 2018 a ), so diurnal habitat use (use of roads) may be another strategy to maximize energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…Grouping can also increase breeding success through alloparental care (e.g., Moehlman, 1979) and decreased predation vulnerability (Kamler et al, 2013a). Sociality can also provide thermoregulatory, energetic and physiological benefits through social thermoregulation (Campbell et al, 2018). Though social thermoregulation is little studied in canids, Hennemann et al (1983) found that crab-eating foxes reduced heat loss and oxygen consumption (a measure of basal metabolic rate) by 5-18% when huddling with a partner, suggesting huddling can significantly impact daily energy expenditure in this and other canid species (Hennemann et al, 1983).…”
Section: Social Structurementioning
confidence: 99%
“…Therefore, thermoregulatory demands, which presumably affect all individuals equally across units of different size, may constrain metabolic needs more than food does. In addition, individual characteristics (e.g., gregariousness) are likely important predictors of variation in glucocorticoid levels, especially where more social partners may provide certain benefits (e.g., thermoregulatory benefits: 27 ). Both of these hypotheses warrant further investigation.…”
Section: Main Textmentioning
confidence: 99%